2018
DOI: 10.1080/21691401.2018.1529677
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on oxygen releasing of HBOC and red blood cells as fluids and factors affecting the process

Abstract: Red blood cells (RBCs) possess intact cyto-architectures while haemoglobin (Hb) is a cell-free, homogeneous solution. Both RBCs and Hb are generalized oxygen carriers. In this paper, kinetic studies on oxygen-releasing of high concentration of Hb and RBCs under various conditions were carried out regarding Hb and RBCs as fluids. Among them, Hb under specific conditions was seen as the simplest Hb-based oxygen carrier (HBOC), Also, factors affecting the oxygen releasing of Hb and RBCs, including osmotic pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…HBOC may play important roles in transfusion medicine and are beneficial to anemia, trauma, and hypoxia-related diseases ( Jahr et al, 2021 ). YQ23 has a reduced affinity for oxygen (compared with free hemoglobin) and the p50 of hemoglobin in YQ23 is about 40 mmHg which is similar to RBC, and the oxygen releasing rate is faster than RBCs when oxygen partial pressure is low ( Zhao et al, 2018 ), which suggested fine oxygen carrying capacity and facilitated rapidly restoring the oxygen content in hypoxic tissues. YQ23 increased the oxygen supply and restored tissue hypoxia, and won opportunity for subsequent treatment ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…HBOC may play important roles in transfusion medicine and are beneficial to anemia, trauma, and hypoxia-related diseases ( Jahr et al, 2021 ). YQ23 has a reduced affinity for oxygen (compared with free hemoglobin) and the p50 of hemoglobin in YQ23 is about 40 mmHg which is similar to RBC, and the oxygen releasing rate is faster than RBCs when oxygen partial pressure is low ( Zhao et al, 2018 ), which suggested fine oxygen carrying capacity and facilitated rapidly restoring the oxygen content in hypoxic tissues. YQ23 increased the oxygen supply and restored tissue hypoxia, and won opportunity for subsequent treatment ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different levels of hemoglobin concentrations in sepsis patients may be due to presenting conditions [4], nutritional deficiencies, inflammatory anemia [5][6][7], hemolysis [8,9], loss of bloodletting, loss of gastrointestinal tract, transfusion expansion, fluid load resulting in hemodilution [10], decreased bone marrow response to erythropoietin [11], inhibition of erythropoietin production by pro-inflammatory cytokines [7,12], response to drugs [13], inappropriate blood transfusion [14] and so on.…”
Section: Introductionmentioning
confidence: 99%